The Network of Middle Eastern and Archipelagic Sufi Scholars: Tracing the Dynamics of Sufism Development in Indonesia - Marsuki; Umi Sumbulah; Helmi Syaifuddin (Teosofia: Indonesian Journal of Islamic Mysticism, 2024)
The network of Middle Eastern and archipelagic Sufi scholars can be traced from various dimensions. The Islamic arrival history in Indonesia was brought by Arab, Persian, and Indian merchants, as well as scholars. This study aims to disclose the formation of the network between Middle Eastern and archipelagic Sufi scholars and uncover the dynamics of the development of Sufi teachings in Indonesia. The method applied is qualitative-descriptive with library research. The data sources are books and scientific works. The data were then analysed using Miles and Huberman, consisting of three activities simultaneously: data reduction, data display, and conclusion. This study revealed that the network of Middle Eastern and Archipelagic Sufi scholars was created through trade, da'wah, marriage, arts, culture, and education. Therefore, the process of Islamization in Indonesia was mostly carried out through the Sufi path because of the cultural similarities between the two. The impact of the network form of these two Sufi scholars shows the dynamics of the development of Sufism from groups that (1) sympathise, those who believe that Sufism is a teaching from the Prophet, and (2) those who are antipathetic and reject the presence of Sufism and tariqa teachings, especially in Indonesia because the Prophet never exemplify these teachings. Contribution: The results of this study provide scientific insight into the arrival of Islam in Indonesia, which occurred more through a Sufi process through a network of Sufi scholars from the Archipelago and the Middle East.